Thermally-induced mechanical behaviour of a single proppant under compression: Insights into the long-term integrity of hydraulic fracturing in geothermal reservoirs. (May 2018) - Bandara, K.M.A.S.; Ranjith, P.G.; Rathnaweera, T.D.; Perera, M.S.A.; Kumari, W.G.P.
Highlights: The effect of temperature on proppant mechanical behaviour was investigated. The different cooling conditions were coupled with the mechanical behaviour. The post-failure of a proppant was analysed. Significant mechanical weakening was observed with increasing temperature. Thermal cracks and the mineralogical alterations seem to be the reason for the weakening process. Abstract: With the increasing demand persisting for energy extraction from geothermal resources, many scientific research studies have been carried out on the performance of proppants to improve the energy extraction process. Knowledge of the after-effects of proppants exposed to realistic geothermal reservoir conditions is crucial. Therefore, the aim of the experimental study reported here was to investigate the mechanical behaviour of a single proppant under incremental loading conditions, and the mineralogical and microstructural alterations due to exposure to elevated temperatures (100 °C, 200 °C, 300 °C and 400 °C) and different cooling conditions (slow cooling and quenching). Significant mechanical weakening, overall strength reduction of 52.19% and 69.74% and Young's modulus reduction of 43.64% and 55.45% for the slow cooling and quenching cooling techniques were observed in a single proppant when the temperature increased from room temperature (25 °C) to elevated temperatures. Scanning electron microscopy revealed the occurrence of thermal cracks inside the proppant microstructure, together with the alteration of the mineral structure, and significant changes in zeolite, Na-feldspar and K-feldspar were observed upon exposure to elevated temperatures. The post-failure behaviour of a single proppant was studied conducting 3-D X-ray computed tomography (CT) scanning. Under normal loading conditions, proppants cleave and generate large fragments like a flower, and this happens suddenly and quite violently through the material. Interestingly, post-failure analysis revealed that the failure mechanism of a single proppant consists of three major stress levels, where initially proppant fails at a high stress level and gains some crushing-associated strength at later stages.